Correlation of Education and Attitude based on the Katz and Stotland approach to Learning Outcomes of ICP PBA UIN Malang Students - Munirah, Munirah; Machmudah, Umi (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah, 2024)
This scientific paper aims to determine attitudes according to the Katz and Stotland Approach and the relationship of education and attitudes towards learning outcomes based on the Katz and Stotland approach. This research uses phenomenological methods carried out in the ICP PBA UIN Maulana Malik Ibrahim Malang Program. The source of data in this study are informants, who were selected by purposive sampling, namely the secretary of the ICP Institute, and students. Data collection was carried out observation, interviews, and documentation techniques. The collected data were analyzed qualitatively using a descriptive-analytical approach. The results of the study show that attitudes according to Katz and Stoland's approach include 3 aspects of response, namely cognitive, affective and conative aspects and education and (attitude) attitudes based on Katz and Stotland's theory have a very good correlation. This is proven by the efforts of the ICP Institute of UIN Maulana Malik Ibrahim Malang in shaping attitudes in the form of character education through excellent programs that have an impact on student learning outcomes.